Advancing genetic testing for deafness with genomic technology. Issue 9 (26th June 2013) - Shearer, A Eliot; Black-Ziegelbein, E Ann; Hildebrand, Michael S; Eppsteiner, Robert W; Ravi, Harini; Joshi, Swati; Guiffre, Angelica C; Sloan, Christina M; Happe, Scott; Howard, Susanna D; Novak, Barbara; DeLuca, Adam P; et al.
Abstract : Background: Non-syndromic hearing loss (NSHL) is the most common sensory impairment in humans.  Until recently its extreme genetic heterogeneity precluded comprehensive genetic testing. Using a platform that couples targeted genomic enrichment (TGE) and massively parallel sequencing (MPS) to sequence all exons of all genes implicated in NSHL, we tested 100 persons with presumed genetic NSHL and in so doing established sequencing requirements for maximum sensitivity and defined MPS quality score metrics that obviate Sanger validation of variants. Methods: We examined DNA from 100 sequentially collected probands with presumed genetic NSHL without exclusions due to inheritance, previous genetic testing, or type of hearing loss. We performed TGE using post-capture multiplexing in variable pool sizes followed by Illumina sequencing. We developed a local Galaxy installation on a high performance computing cluster for bioinformatics analysis. Results: To obtain maximum variant sensitivity with this platform 3.2–6.3 million total mapped sequencing reads per sample were required. Quality score analysis showed that Sanger validation was not required for 95% of variants. Our overall diagnostic rate was 42%, but this varied by clinical features from 0% for persons with asymmetric hearing loss to 56% for persons with bilateral autosomal recessive NSHL. Conclusions: These findings will direct the use of TGE and MPS strategies for genetic diagnosis for NSHL. Our diagnostic rate highlights the need for further research on genetic deafness focused on novel gene identification and an improved understanding of the role of non-exonic mutations.  The unsolved families we have identified provide a valuable resource to address these areas.